(untitled) (The Pakistan Development Review, 1981)
This paper reviews the theoretical and empirical evidence about interactions between trade policy instruments and domestic factor markets and their role in affecting the labour intensity of industry mix and choice of techniques in a number of developing countries. Using estimates of the elasticities of substitution in the manufacturing sector ,statistical evidence is presented to determine the impact of trade policy on industrial employment. There is a strong presumption that the phenomena under review were mainly responsible for low rates of employment growth in the industrial sector in those countries where distortions were sizeable.